Intensified Competition and The Impact on Credit Ratings in the RMBS market. Issue 2 (11th March 2023) - van Breemen, Vivian M.; Fabozzi, Frank J.; Vink, Dennis
Abstract: In this paper, we empirically investigate the impact of intensified competition on rating quality in the credit rating market for residential mortgage‐backed securities (RMBS) in the period 2017–2020. We provide evidence that competition between large credit rating agencies (CRAs) (Moody's and Standard & Poor's) and newer smaller ones (Dominion Bond Rating Service Morningstar and Kroll Bond Rating Agency) creates credit rating inconsistencies in the RMBS market. While a credit rating should solely represent the underlying credit risk of a RMBS, irrespective of the competition in the market, our results show that this is not the case. When competitive pressure is higher, both large and small CRAs tend to adjust their rating standards (smaller CRAs react to large CRAs and vice versa).